Effects of daytime floatation-restricted environmental stimulation therapy on nocturnal cardiovascular physiology, sleep, and subjective recovery in collegiate student-athletes: a comprehensive observational study - Vatne, E.; Merrigan, J. J.; Stone, J. D.; Saenz, C.; Kraemer, W. J.; Hagen, J. A. (The Journal of Strength and Conditioning Research, 2025)
The primary aim of this study was to explore the relationship between floatation-restricted environmental stimulation therapy (floatation-REST) and nocturnal cardiovascular physiology and sleep in collegiate athletes. The secondary aim was to describe the perceived changes in soreness, mood, fatigue, energy level, and overall experience after floatation-REST in collegiate athletes. Data included 214 records of nocturnal cardiovascular physiology and sleep collected using an acceptably valid and reliable wearable device (Oura Ring, Oura Health, Oulu, Finland) from 97 athletes (52.57% women) on 12 varsity teams, and 2,319 survey responses collected immediately after floatation-REST from 898 athletes (48.88% women) on 36 varsity teams. Nocturnal cardiovascular physiology was assessed through resting heart rate, heart rate variability, and respiration rate, while sleep was summarized using total sleep time, time in bed, and sleep efficiency. The representation of teams was varied, with football and men's and women's swimming heavily represented. Male and female athletes were analyzed separately to prevent overlooking sex-specific physiologic differences. Resting heart rate was significantly lower after floatation-REST than at night immediately before the session in female athletes (p < 0.001, effect size [ES] = -0.223) and male athletes (p < 0.001, ES = -0.186). Heart rate variability and sleep metrics showed no specific changes. In total, 98.7% of athletes reported an overall positive floatation-REST experience, and 85.3% felt better postsession, citing reduced soreness, stress, and fatigue, with improved energy. Thus, although more research is needed, these data provide a positive outlook for the use of this recovery technology in collegiate athletes.